Pertanggungjawaban Hukum Pemerintah Daerah terhadap Jalan Rusak (Studi Pasal 1365 KUHPerdata) - Ika Ayudyanti; Zakiah Noer (Cattleya Darmaya Fortuna, 2026)
The escalation of road infrastructure dysfunction in Indonesia represents a systemic failure that implicates public safety degradation and multidimensional losses for road users. This research aims to analyze the qualification of Tort (Perbuatan Melawan Hukum) by Regional Governments based on Article 1365 of the Indonesian Civil Code and examine the limitations of their liability within the framework of Law Number 22 of 2009 concerning Traffic and Road Transport (UU LLAJ). Employing a normative legal research method with a statutory approach and a case approach, the results indicate that the neglect of road maintenance is qualified as an administrative omission that satisfies the cumulative constitutive elements of a tort, including fault, damage, and a causal relationship characterized as conditio sine qua non. The legal accountability of Regional Governments is complementary, wherein the penal sanctions in Article 273 of the UU LLAJ synergize with civil restitution instruments to guarantee restorative justice. Although constrained by the principle of proportionality and the potential for force majeure defenses, this regulatory synchronization affirms that budgetary restrictions cannot negate the legal obligation of regional authorities to conduct risk mitigation and accelerative infrastructure rehabilitation. As a strategic solution, this study recommends the digitalization of road monitoring systems and the establishment of a Road Infrastructure Guarantee Fund to optimize legal certainty and the protection of subjective public rights to high-integrity public services.